Silicon Fertilization Enhances Photosynthetic Activity and Sugar Metabolism in Sugarcane Cultivars under Water Deficit at the Ripening Phase - Camargo, Mônica Sartori; Baltieri, Gustavo Jonas; Santos, Hariane Luiz [UNESP]; Carnietto, Melina Rodrigues Alves [UNESP]; dos Reis, André Rodrigues [UNESP]; Pacheco, Ana Claudia; de Almeida Silva, Marcelo [UNESP] (Springer Nature, 2023)
Silicon (Si) has been associated with minimizing water deficit damage in several plants, but its effects on physiological aspects and gas exchange responses for sugarcane during the ripening phase are still scarce. Therefore, this study aimed to determine whether Si fertilization enhances physiological and gas exchange responses, biomass and sugar production in response to water deficit during the ripening phase of sugarcane, and whether these responses are similar in drought-tolerant and drought-sensitive cultivars. A greenhouse experiment was conducted using two sugarcane cultivars (RB855536 is drought-sensitive; RB867515 is drought-tolerant) without and with Si (0 = zero and 1000 kg−1 Si; -Si and + Si) under well-watered or water deficit conditions at the ripening phase. The biometric, physiological, and gas exchange measurements were independently influenced by the water deficit, cultivar, and Si. The leaf Si concentration, chlorophyll a (Chla), carotenoids, net CO2 assimilation rate (A), electron transport rate (ETR), plant transpiration (E), stomatal conductance (gs), and sugar content in stalks increased with Si, and electrolyte leakage (EL), plant length, leaf area (LA), and stalk fresh biomass decreased. Water deficit decreased the leaf water potential (ψW), fresh biomass of leaves, and LA. RB867515 showed higher LA, plant length, and fresh leaves biomass, while RB855536 showed superior leaf Si, Chla, Chlb, carotenoids, A, ETR, E, sugar content, and EL and lower ψW. Si fertilization promotes enhancement in some physiological and gas exchange aspects and increased sugar contents in stalks, independent of the water deficit at ripening phase or the drought tolerance of sugarcane cultivars.
Keywords: Drought stress; Physiological aspects; Saccharum spp; Silicate; Soil